1992
DOI: 10.1002/pd.1970120803
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic, haematological, and biochemical findings in a fetus with Caffey disease

Abstract: An early case of prenatal Caffey disease is reported. Ultrasound examination performed at 20 weeks showed major angulations of long bones, but both ultrasound scan and X-rays failed to make the differential diagnosis between Caffey disease and lethal osteogenesis imperfecta. A cordocentesis allowed us to find important biological abnormalities. The pregnancy was terminated after the rapid development of hydrops fetalis. The definitive diagnosis of Caffey disease was obtained by special X-ray and pathological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
0
31
1
Order By: Relevance
“…The condition usually occurs in young infants (i.e., before 5 months of age) and is occasionally seen in neonates. Another form of infantile cortical hyperostosis, a lethal prenatal form, has been proposed [Lecolier et al, 1992]. The authors found angulations of long bones, an apparent rib fracture and polyhydramnios at 20 weeks of gestation in a pregnancy aborted at 23 weeks due to fetal-placental anasarca.…”
Section: Introductionmentioning
confidence: 98%
“…The condition usually occurs in young infants (i.e., before 5 months of age) and is occasionally seen in neonates. Another form of infantile cortical hyperostosis, a lethal prenatal form, has been proposed [Lecolier et al, 1992]. The authors found angulations of long bones, an apparent rib fracture and polyhydramnios at 20 weeks of gestation in a pregnancy aborted at 23 weeks due to fetal-placental anasarca.…”
Section: Introductionmentioning
confidence: 98%
“…Spontaneous remission is the usual outcome but relapses and long-term complications while uncommon can occur [2]. Diagnosis is confirmed with elevated alkaline phosphatase levels and plain radiographs [8]. Subperiosteal new bone formation with progressive cortical thickening can be seen in any bone except the vertebrae and phalanges.…”
Section: Discussionmentioning
confidence: 98%
“…Tenderness is deep and firm but skin changes (erythema, discolouration) are not seen. The mandible is most frequently involved followed by the clavicle and ulna, and involvement is usually asymmetrical [8]. Histologically, the periosteum is thickened, there is subperiosteal immature lamellar bone and a vascular fibrous infiltrate in the medulla at the affected site [9].…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal examination confirmed Caffey disease with osteosclerosis that led to thickened clavicles and ribs. 11 Severe expansion of the bowed long bones showed a cortical new bone formation. B, Despite the initial false impression of a small chin on surface rendering, a midline sagittal view (top right) provides evidence that the chin is actually well developed.…”
Section: Discussionmentioning
confidence: 99%